Шляхи християнства на Русь (легендарні й реальні) - Котляр, М.Ф. (Український історичний журнал, 2008)
Розглядається тривала історія проникнення християнського віровчення на Русь. Аналізуються легендарні версії християнізації Русі – прихід апостола Андрія на київські гори, свідчення арабських авторів про численних купців-русів, які видавали себе за християн. Відзначено, що головним шляхом християнства на Русь, особливо із середини IX ст., був візантійський. The article examines the long history of penetration of Christian doctrine into Rus. The author analyzes legendary versions of conversion to Christianity of Rus' – coming of St.Andrew onto Kyiv mounts, Arabic authors' evidence about numerous merchants, residents of Rus', which posed as Christians. The author points out that the main way of Christianity to Rus' especially since the middle IX c. was the Byzantine one.